Pengaruh Pembelajaran Berbasis Masalah terhadap Keterampilan Pemecahan Masalah Peserta Didik Kelas VIII dalam Pembelajaran IPA - Aulianur Fadila; Febri Yanto; Firda Az Zahra; Tuti Lestari (SEMESTA: Journal of Science Education and Teaching, 2026)
This study examined the effect of the Problem-Based Learning (PBL) model on eighth-grade students’ problem-solving skills in science learning, particularly on the topic of the human digestive system. A quasi-experimental method with a non-equivalent control group design was employed. The sample consisted of two classes selected through purposive sampling: one experimental class taught using the PBL model and one control class taught using conventional instruction. Data were collected using an essay test administered as pretest and posttest, supported by observation sheets and a student response questionnaire. The data were analyzed using descriptive and inferential statistics. The results indicate that students taught using the PBL model achieved significantly higher problem-solving skills than those taught using conventional methods. In addition, the implementation of the PBL model was categorized as very well implemented, and students showed very positive responses toward the learning process. These findings suggest that the Problem-Based Learning model is effective and feasible to improve students’ problem-solving skills in science learning and can be recommended as an alternative instructional approach in junior high school science classrooms.